Pengembangan Perangkat Pembelajaran Melalui Pendekatan Konstruktivistik dengan Metode Five E (5E) Stages Learning Cycle untuk Meningkatkan Hasil Belajar dan Keterampilan Proses Sains - Mislan Sasono; Farida Huriawati; Andista Candra Yusro (Universitas PGRI Kanjuruhan Malang, 2017)
Research aims to implement and develop the shape of the natural science/physics as device learning to enhance science process skills and the results of learning through constructivist approach with (5E) stages of material objects and the learning cycle to its elementary school students of classes V. This research includes Research and Developmental research (R&D). In developing this form of learning devices used stage design (design), stage of development (develop), stages of dissemination (disseminate). The form of a learning device successfully developed by disseminaing once to three times, and subject learning classes V at Kanigoro elementary school. Any form of learning devices developed validated by researchers with triangulation. Activities undertaken by students and student learning outcomes during learning recorded as quantitative data and analyzed in qualitative descriptive. The shape of the device successfully developed through learning method 5E learning cycle stages was work Sheets, learningÃ‚Â implementation plan, the evaluation sheet of the product. Based on the descriptive analysis of the obtained conclusions that the learning that has been developed successfully process skills increase students and student learning outcomes. Science process skills improvement students learning I, II, and III, i.e., 70.79%, 73.97%, as well as analysis results 78.10% average value of pre test and post test students experience increased i.e. 31 points from the average value of 33 pre test and average value of post test of 64.Ã‚Â Keywords: Method Five E (5E) Learning Cycle, Results Learning, Science Process SkillsÃ‚Â Penelitian ini bertujuan menerapkan dan mengembangkan bentuk perangkat pembelajaran IPA/Fisika untuk meningkatkan keterampilan proses sains dan hasil belajar melalui pendekatan konstruktivistik dengan metode (5E) learning cycle materi benda dan sifatnya siswa SD kelas V. Penelitian ini termasuk penelitian Research and Developmental (R&D). Dalam mengembangkan bentuk perangkat pembelajaran digunakan tahap perancangan (design), tahap pengembangan (develop), tahap penyebaran (disseminate). Bentuk perangkat pembelajaran yang berhasil dikembangkan didiseminasikan satu kali untuk tiga kali pembelajaran, subjek penelitian siswa kelas V SD Kanigoro. Setiap bentuk perangkat pembelajaran yang dikembangkan divalidasi oleh peneliti dengan triangulasi. Aktivitas yang dilakukan oleh siswa dan hasil belajar siswa selama pembelajaran dicatat sebagai data kuantitatif dan dianalisis secara deskriptif kualitatif. Bentuk perangkat pembelajaran yang berhasil dikembangkan melalui metode 5E learning cycle adalah LKS, RPP, lembar evaluasi produk. Berdasarkan analisis deskriptif diperoleh kesimpulan bahwa perangkat pembelajaran yang telah dikembangkan berhasil meningkatakan keterampilan proses siswa dan hasil belajar siswa. Peningkatan keterampilan proses sains siswa setiap pembelajaran I, II, dan III yaitu 70.79%, 73.97%, 78.10% serta analisis hasil nilai rata-rata pre test dan post test siswa mengalami peningkatan yaitu 31 poin dari nilai rata-rata pretes sebesar 33 dan nilai rata-rata postes sebesar 64.Ã‚Â Kata Kunci: Metode Five E (5E) Learning Cycle, Hasil Belajar, Keterampilan Proses Sains